ISLAMIC INVESTMENT IN INDONESIA BEFORE AND DURING PANDEMIC OF COVID-19: A BIBLIOMETRIC STUDY - akhmad kusuma wardhana; ririn tri ratnasari; hasna fauziana (Berkala Akuntansi dan Keuangan Indonesia, 2023)
Indonesia had a potential for Islamic investment development because of its biggest number of Muslims in the world. Islamic investment through the sharia capital market was positive even during the pandemic of COVID-19. This study has a purpose to observe the correlation between topic-related Islamic investment in Indonesia along with the shift of trend of topics before and during COVID-19. There were 1072 samples gathered from Scopus website with keyword “Islamic”, “investment”, and “Indonesia”. The data were analyzed using bibliometric method. This study used Vosviewer and R Studio to analyzed the data. The result showed that there were correlation between